Paper 04: The effect of prescribing patterns on utilization of opioid medication in ACL reconstruction: A randomized, prospective trial. Issue 7 (30th July 2022) - Hall, Anya; Hahn, Alexander; Pepe, Matthew; Tucker, Bradford; Tjoumakaris, Fotios; Johnson, Emma
Objectives: During the 21 st century, opioid medication prescription and consumption has increased, which has led to an increase in opioid abuse, dependence, and fatal overdoses. Health care providers, particularly surgeons, have recently focused on decreasing the amount of opioids prescribed, as overprescribing is a known cause contributing to the opioid epidemic. Patients undergoing anterior cruciate ligament reconstruction (ACLR) would especially benefit for the identification of an ideal opioid prescription amount for post-op pain, as the average age of patients undergoing ACLR is 29.8 years old, which falls within the age group that experienced the largest increase in opioid related deaths between 2001 and 2016. It is unknown if prescribing patterns change patient behavior related to opioid consumption. The purpose of this randomized, prospective trial was to evaluate the effects of different quantities of prescribed opioid tablets on opioid utilization by patients, post-operative pain, and patient satisfaction following ACL reconstruction. Methods: This study was a prospective, randomized trial enrolling patients undergoing primary ACLR following ACL tear. Patients were randomly assigned to one of 3 prescription groups pre-operatively: 15 tablets, 25 tablets, or 35 tablets of oxycodone-5mg. Standard of care nerve blocks were utilized in all patients in addition to general anesthesia for the surgical procedure. Patients were instructed to take acetaminophen and NSAIDs as needed with the opioid medication to be used for "breakthrough" pain. Exclusion criteria included concomitant procedure other than meniscectomy or meniscal repair, ACL revision, history of chronic pre-operative opioid use, history of substance abuse, pregnancy, or workman's compensation claims. Patients in all 3 groups were asked to complete pain and medication logs 2 times a day for the first 14 days post-operatively, along with an opioid medication satisfaction survey at 2 weeks, and IKDC questionnaires before surgery and up to 6 months post-operatively. Demographics and complication information were gathered from the medical record. Requests for prescription refills were recorded as well. Analysis assessed for statistical differences in post-op pain and medication usage. All usage of narcotics was verified with the state database monitoring system for narcotic pain medication. Results: One hundred thirty patients were included in the analysis (41 who received 15 oxycodone tablets, 40 who received 25 oxycodone tablets, and 49 who received 35 oxycodone tablets). There were no significant differences between the two groups in mean age at surgery (33.6 vs. 31.6 vs 33.3; P=0.328), BMI (27.7 vs 26.1 vs 25.7; P=0.525), or sex ratio (24M/17F, 20M/19F, 25M/24F; P=0.735). There were also no significant preoperative differences in subjective pain and function, as measured by IKDC scores (46.8 vs 48.7 vs 46.5; P=0.794). There were no significant differences in mean total morphine milligram equivalents (MME) consumed between the three groups (72.3 in the 15 tablet group, 61.9 in the 25 tablet group, 78.1 in the 35 tablet group; P>0.05). There was a significant difference between those who received 15 tablets and those who received 25 and 35 tablets when asked if they thought they were prescribed too few/too many narcotics, with a greater percentage of the 15 tablet group reporting that they felt they received too few at 20.6%, (P=0.05) as depicted in Figure 1. Despite this difference, there was no significant difference between the three groups on subjective morning or afternoon pain for the first 14 days after surgery, total opioid pills consumed, patient satisfaction on ability of the narcotic to treat their condition, patient satisfaction on amount of pain relief they experienced since surgery, or patient satisfaction regarding the amount of narcotics initially prescribed after surgery. Finally, there was no difference between the three groups on postoperative function at 2 weeks, 6 weeks, 3 months, and 6 months, as measured by IKDC scores (Figure 2). Conclusions: Despite a significantly larger portion of the group who received 15 oxycodone tablets reporting that they felt they received too few opioid tablets, there was no difference between those who received 15, 25, or 35 oxycodone-5mg tablets in reported pain levels, opioid consumption, or any satisfaction metrics. In addition, there was no difference between the three groups in pain and function as reported in the IKDC surveys. Given these results, giving lower quantities of opioid medication appears to be as effective in appropriately controlling post-operative pain as higher quantities, and may help to limit amount of opioids prescribed and possible diversion of unused prescription opioid medication.